Engineered Magnetic Carbon-Based Adsorbents for the Removal of Water Priority Pollutants: An Overview. (27th October 2021) - Reynel-Ávila, H. E.; Camacho-Aguilar, K. I.; Bonilla-Petriciolet, A.; Mendoza-Castillo, D. I.; González-Ponce, H. A.; Trejo-Valencia, R.
Abstract : This review covers the preparation, characterization, and application of magnetic adsorbents obtained from carbon-based sources and their application in the adsorption of both inorganic and organic pollutants from water. Different preparation routes to obtain magnetic adsorbents from activated carbon, biochar, hydrochar, graphene, carbon dots, carbon nanotubes, and carbon nanocages, including the magnetic phase incorporated on the solid surface, are described and discussed. The performance of these adsorbents is analyzed for the removal of fluoride, arsenic, heavy metals, dyes, pesticides, pharmaceuticals, and other emerging and relevant water pollutants. Properties of these adsorbents and the corresponding adsorption mechanisms have been included in this review. Overall, this type of magnetic adsorbents offers an alternative for facing the operational problems associated to adsorption process in water treatment. However, some gaps have been identified in the proper physicochemical characterization of these adsorbents, the development of green and low-cost preparation methods for their industrial production and commercialization, the regeneration and final disposal of spent adsorbents, and their application in the multicomponent adsorption of water pollutants.